2010
DOI: 10.1017/s1355617710001645
|View full text |Cite
|
Sign up to set email alerts
|

Deteriorated Executive Functions in Patients with Successful Surgery for Pituitary Adenomas Compared with Other Chronically Ill Patients

Abstract: Pituitary adenomas, even after successful treatment, are associated with cognitive impairments. It is unclear whether these deficits are a consequence of unspecific factors associated with having a chronic illness and whether the cognitive dysfunctions exceed those of other chronically ill patients. Thirty-eight patients with transsphenoidal surgery for pituitary adenomas and 38 patients undergoing L-thyroxine replacement therapy after thyroid surgery were studied neuropsychologically with established tests. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Furthermore, compromised social and physical functioning, energy levels and emotional reactions, as well as increased anxiety, depression and fatigue have all been reported in women treated for microprolactinomas compared with controls . In pituitary adenomas, generally, including NFAs, cognitive defects including decreased attention, executive control, working memory, verbal memory and executive functioning have all been reported. More specifically, assessments by standardized personality questionnaires have revealed neurotic, harm‐avoidant personality patterns in patients with acromegaly and NFAs, reduced novelty seeking behaviour in patients with acromegaly, as well as less active coping strategies and increased avoidance behaviour in all subjects with pituitary adenomas …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, compromised social and physical functioning, energy levels and emotional reactions, as well as increased anxiety, depression and fatigue have all been reported in women treated for microprolactinomas compared with controls . In pituitary adenomas, generally, including NFAs, cognitive defects including decreased attention, executive control, working memory, verbal memory and executive functioning have all been reported. More specifically, assessments by standardized personality questionnaires have revealed neurotic, harm‐avoidant personality patterns in patients with acromegaly and NFAs, reduced novelty seeking behaviour in patients with acromegaly, as well as less active coping strategies and increased avoidance behaviour in all subjects with pituitary adenomas …”
Section: Introductionmentioning
confidence: 99%
“…Inhibitory control impairment still exists after the surgery of pituitary adenoma, which is consistent with some points of previous studies. 22,23 This finding demonstrates that the inhibitory control function is impaired from brain injury or changes in neuroanatomical structures.…”
Section: Discussionmentioning
confidence: 79%
“…At present, the number of reported patients that underwent neuropsychological evaluation after being considered adequately treated for acromegaly is still limited. Most studies evaluating cognitive function found worse scores on memory and executive functioning both in patients treated for acromegaly and for non-functioning adenomas, when compared to controls [10][11][12][13][14]. In the cohort of patients successfully treated for acromegaly at our center, cognitive function did not differ between acromegaly patients and matched controls or between acromegaly patients and patients treated for non-functioning adenomas [15].…”
mentioning
confidence: 70%